1951
DOI: 10.3382/ps.0300343
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Early Growth in Domestic Fowl

Abstract: From a reasonably intensive review of the animal science literature, two general situations were noted. First, ample evidence suggests the more careful use of the term rate of growth, or growth rate(s); second, a new method is needed to analyze growth-in-time studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1952
1952
1985
1985

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Brenner 1964) or exponential equations (e.g. Brant 1951) has the complementary disadvantage that the asymptotes of growth curves cannot be compared. The fitting of asymptotic equations to growth curves yields both kinds of information and has been applied to the growth of birds, for example by Taylor & Roberts (1961) and G. A.…”
Section: Intraspecific Variationmentioning
confidence: 99%
“…Brenner 1964) or exponential equations (e.g. Brant 1951) has the complementary disadvantage that the asymptotes of growth curves cannot be compared. The fitting of asymptotic equations to growth curves yields both kinds of information and has been applied to the growth of birds, for example by Taylor & Roberts (1961) and G. A.…”
Section: Intraspecific Variationmentioning
confidence: 99%
“…The most extensively applied mathematical models, characterizing the whole course of growth including asymptotic final weight and inflection point parameters where the autoacceleration phase of growth passes into autoretardation phase, are monomolecular, logistic, Gompertz and Bertalanffy functions which are special cases of the generalized four‐parameter Richards function with variable inflection point position (R ichards 1959, E isen et al 1969, F itzhugh 1976, M c C arthy , B arker 1979 and others). Shorter growth periods can be expressed by simple functions, e. g. power (R oberts 1964, T anabe , S aeki 1964), exponential (B rody 1945, B rant 1951) or quadratic function (S usaki 1966). A critical analysis of various mathematical model applications to the growth of chickens was presented in the study of G rossman and B ohren (1982).…”
Section: Introductionmentioning
confidence: 99%
“…Goodman and Godfrey (195U) in a study of body weight of broilers, found that 11 percent of the variance in weight at 9 weeks of age was due to hatch effects. Brant (1951) reported that the differences in early growth between hatches were greater than the differences between the breeds and strains used.…”
Section: List 0? Tables (Continued)mentioning
confidence: 99%